The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.ydbio.2004.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Engrailed and polyhomeotic maintain posterior cell identity through cubitus-interruptus regulation

Abstract: In Drosophila, the subdivision into compartments requires the expression of engrailed (en) and hedgehog (hh) in the posterior cells and of cubitus-interruptus (ci) in the anterior cells. Whereas posterior cells express hh, only anterior cells are competent to respond to the hh signal, because of the presence of ci expression in these cells. We show here that engrailed and polyhomeotic (ph), a member of the Polycomb Group (PcG) genes, act concomitantly to maintain the repression of ci in posterior compartments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…These groups also identified lethal alleles of cg and identified cg as a genetic repressor of the GLIfamily protein Cubitus interruptus (Ci) in the posterior compartment of the wing imaginal disc. Further, other studies had shown that the PcG protein Ph directly represses ci, suggesting that ci is a PcG target (35). These data suggested to us that Cg was a good candidate for a PRE DNA-binding protein.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…These groups also identified lethal alleles of cg and identified cg as a genetic repressor of the GLIfamily protein Cubitus interruptus (Ci) in the posterior compartment of the wing imaginal disc. Further, other studies had shown that the PcG protein Ph directly represses ci, suggesting that ci is a PcG target (35). These data suggested to us that Cg was a good candidate for a PRE DNA-binding protein.…”
Section: Resultsmentioning
confidence: 53%
“…Note that the level of H3K27me3 is insignificant throughout the ci region; therefore, ci does not appear to be a target for PRC2 in larvae. Interestingly, the upstream Ph peaks were partially contained within a reporter construct that has been shown to recruit Ph to a ci-reporter transgene (35). These data suggest that Cg may participate in the recruitment of Ph in the absence of PRC2.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Chromatin immunoprecipitation: Chromatin immunoprecipitation (ChIP) was performed according to described procedure (Chanas et al 2004). The analysis of DNA obtained in ChIP was done by semiquantative radioactive PCR as described above.…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…The larval wing imaginal disc, which gives rise to the adult wing, is subdivided into nonintermingling anterior (A) and posterior (P) compartments. En is present in the P compartment, where it acts as a transcription factor to establish and maintain P cell identity (Lawrence and Morata, 1976;Hidalgo, 1994;Zecca et al, 1995;Chanas et al, 2004). En is also known to be expressed (Blair, 1992) and to function in a few cell rows in the A compartment that abut the A/P boundary (Hidalgo, 1994).…”
Section: Introductionmentioning
confidence: 99%